Does trunk flexion affect knee extensor moments during landing in volleyball players? - Janssen, I.; Steele, J.; Munro, B.; Brown, N. (Journal of Science and Medicine in Sport, 2011)
Introduction: Volleyball players suffer a disproportionately high number of overuse knee injuries, particularly when performing blocking movements. Blocking is characterised by numerous jump-land manoeuvers, typically performed with low trunk flexion upon landing due to constraints imposed by the volleyball net. It is possible that these constraints to trunk flexion affect knee extensor moments during landing, whereby excessive knee extensor moments have been associated with overuse knee injuries. The aim of this research was to examine the influence of trunk flexion on knee extensor moments during landing from block jump landings. Methodology: Fifteen male volleyball players (24.3 +/- 5.5 years; 82.80 +/- 12.8 kg; 1.87 +/- 0.05 m) performed five trials of a slide-step block jump landing moving to the left. Kinematic (250 Hz; VICON) and kinetic (1500 Hz; Kistler force platforms) data were collected and internal knee extensor moments for the lead (left) and trail (right) limbs calculated for each subject. Paired t-tests determined whether there were significant (p . 0.05) differences in knee extensor moments between the lead or trail limb and a Pearson's correlation was used to determine the relationship between knee extensor moment and trunk flexion during landing. Results and Discussion: A significantly higher knee extensor moment was generated by the lead limb during landing compared to the trail limb (2.66 Nm/kg vs. 2.26 Nm/kg; p = 0.007), suggesting that movement direction affects the knee extensor moments generated during landing. As court position determines movement direction, this result may help identify which volleyball athletes are susceptible to knee injuries, particularly to the lead limb. No significant relationship was found between trunk flexion at the time of the peak knee extensor moment and knee extensor moment (p = 0.577 lead limb; p = 0.249 trail limb). This suggests that athletes employ a range of trunk flexion angles during landing (range = -14.-34.) and this does not affect knee extensor moments in a systematic way. Conclusion: In a volleyball-specific movement, trunk flexion was not significantly related to the knee extensor moment during landing. The varying amount of trunk flexion employed by volleyball players may explain this finding with some athletes utilising a trunk extension strategy potentially to avoid touching the net. Further research is required to investigate the effect of trunk rotation and lateral flexion on frontal and transverse plane moments during these landings to provide insight into factors contributing to knee injuries in volleyball players, particularly during blocking.